GAMIFIKASI PEMBELAJARAN TEMATIK MENGGUNAKAN APLIKASI QUIZIZZ SUPER UNTUK MENINGKATKAN RETENSI INGATAN SISWA KELAS IV - Sulistyowati (PT Cendekia Education Center, 2025)
Thematic learning in elementary schools still faces the problem of low student memory retention due to less interactive instructional practices and limited use of educational technology. In fact, thematic learning requires active student engagement to ensure long-term understanding and retention of learning materials. This study aims to examine the implementation of gamified thematic learning using the Quizizz Super application to improve the memory retention of fourth-grade students. The research subjects consisted of fourth-grade students and classroom teachers directly involved in gamification-based thematic learning. This study employed a qualitative approach with a case study design grounded in grounded research principles. Data were collected through desk review, observation, interviews, questionnaires, and Focus Group Discussions (FGD). Data analysis was conducted through data reduction, data display, and conclusion verification. The results indicate that the implementation of gamification using Quizizz Super enhances student engagement, facilitates better understanding of thematic content, and strengthens students’ memory retention of the learning materials.